An investigation into the strength of the 52-week high momentum strategy in the United States : a thesis presented in partial fulfillment of the requirements of the degree of Masters of Business Studies in Finance at Massey University, Palmerston North, New Zealand - Cahan, Rachael Marie (Massey University, 2008)
This thesis extends the 52-week high momentum literature, which was first published by George and Hwang in 2004, by stressing the parameters of the trading strategy to investigate its robustness. George and Hwang, in their seminal paper, find that the ratio of a stock’s close price to its 52-week high price is a good predictor of future returns. The thesis stresses various parameters of the strategy - such as the percent of total stocks bought and sold each period – and applies the strategy over different time periods – such as bull and bear markets. The study finds that the strategy is more profitable over the later half of the data set due to underperformance in bear markets such as the 1929 market crash and subsequent Great Depression. The results also show a significant difference in profitability between bull and bear market periods. The second half of the thesis looks at a new area in momentum, the absolute 52-week high. The strategy buys stocks whose price has increased over the previous six months, and who also close to their 52-week high price. Stocks are only bought (sold) if their price has increased (decreased) over the past six months and is close to (far from) the 52-week high price. The aim is to cut out stocks that are considered to be underperforming in the 52-week high momentum strategy, leaving only true winner and loser stocks. This strategy was found to increase the strength of the 52-week high momentum strategy, and the results show that there is no longer a significant difference between bull and bear market returns.
Keywords: Stock prices; Bear market; Bull market; 52-week high momentum strategy; Fifty-two-week high momentum strategy; United States; Stock price predictions; Trading strategy; Fields of Research::350000 Commerce, Management, Tourism and Services::350300 Banking, Finance and Investment